Genetic screening and mutation identification in a rare canine breed, the Drentsche patrijshond. Issue 1 (13th May 2015) - Shaffer, Lisa G; Ramirez, Christina J; Sundin, Kyle; Carl, Casey; Ballif, Blake C
Abstract : The Drentsche patrijshond (Drent) is a relatively rare breed that is used as a versatile hunting dog. Although inherited diseases occur in this breed, no genetic mutations were previously known to contribute to these inherited disorders. Thirteen Drents were screened for 142 known disease‐associated mutations that occur in domestic dogs. Of these, two mutations were identified to segregate in three pedigrees: mutations for hyperuricosuria and von Willebrand disease type 1. This information can be used to screen Drents before breeding to improve the health of the breed and to avoid producing affected dogs and emphasises the importance of genetic screening for inherited diseases in rare breeds.